3D MODELING OF ARCHITECTURAL STRUCTURE BY PHOTOGRAMMETRY METHOD - A CASE STUDY „CELE KULA“IN NIS - Zlata Tosic; Sonja Krasic; Milica Veljkovic; Bogdan Kostic (Journal of Industrial Design and Engineering Graphics, 2021)
Photogrammetry has a large use in different areas. One of them is architectural practice. Photogrammetry is one of the suitable methods for production of models of existing objects through photography. It represents collecting specific data from photography which is two dimensional, in other to get three dimensional model of object (3D). Models can be done for different purposes. This paper shows the whole procedure of making a model of “Cele-kula“, which represents cultural and historical heritage, in order to promote tourism in Niš. The three dimensional model is constructed in software “Sketch Up” as a part of the project “3D Niš”.